2000
DOI: 10.1016/s1388-9842(00)00111-2
|View full text |Cite
|
Sign up to set email alerts
|

Progressive cardiac dysfunction in adriamycin‐induced cardiomyopathy rats

Abstract: Cardiotoxicity is a limiting factor in the treatment of cancer with adriamycin. We administered adriamycin by a method which minimizes the risk of peritonitis in an adriamycin-induced cardiomyopathy rat model. Sixty male Wistar rats were given Ž . 1 mgrkg of adriamycin intraperitoneally 15 times over a 3-week period total dose, 15 mgrkg to induce the cardiomyopathy model. Fifteen control rats received 10 mlrkg body wt. saline 15 times over 3 weeks. The animals were observed for 12 weeks and assessed for mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…During the acute phase of treatment, the adult rodent's left ventricular dysfunction is not consistent and in general is moderate (Luo et al, 1997;Teraoka et al, 2000). Our recent study on maternal and fetal cardiac function showed no acute dysfunction after anthracycline administration during pregnancy (Gziri et al, 2012b).…”
Section: Discussionmentioning
confidence: 86%
“…During the acute phase of treatment, the adult rodent's left ventricular dysfunction is not consistent and in general is moderate (Luo et al, 1997;Teraoka et al, 2000). Our recent study on maternal and fetal cardiac function showed no acute dysfunction after anthracycline administration during pregnancy (Gziri et al, 2012b).…”
Section: Discussionmentioning
confidence: 86%
“…This is in contrast to data from human patients in which cumulative doses of Dox typically leads to an increase in end diastolic pressure. However, work by others suggests a Dox-induced increase in end diastolic pressure is a function of time such that at 4 weeks after Dox injection there is no change, whereas at 12 weeks after injection there is an increase in left ventricular diastole diameter (Teraoka et al, 2000). Thus, caution should be used comparing our results, using analysis at 3 days after injection from a single dose of Dox in rats, to humans.…”
Section: Protection From Doxorubicin Cardiotoxicity Using Ad 198 227mentioning
confidence: 81%
“…(2) Therefore, measurement of cardiospecific biomarkers can be a valid diagnostic tool for early identification, assessment, and monitoring of cardiotoxicity. Previous cardiotoxicity models include long term exposure to doxorubicin for [5][6][7][8][9][10][11][12] weeks. (5-7) LTMs are time consuming, and represent long-time stress for the animals, and high mortality rates have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…(5-7) LTMs are time consuming, and represent long-time stress for the animals, and high mortality rates have been reported. (8,9) Therefore, it is of interest to develop and test short-time models (STM) when studying cardiotoxicity of anthracyclines. A combination of in vivo and ex vivo animal models has the advantage that it includes relevant pharmacokinetic phases after administration of drugs in vivo.…”
Section: Introductionmentioning
confidence: 99%